Effect of aluminum concentration on microstructure and evolution behavior of oxide layer on NiAlSiY coating at 500 ℃. (1st April 2020) - Wei, Yao; Zheng, Shaoxian; Pu, Jibin; Zhou, Dapeng; Wang, Liping; Guo, Wuming; He, Guangyu
Highlights: The NiAlSiY coating has a layered oxide layer after oxidation for 2 h, the outer layer is NiO, and the inner layer is Al2 O3 . TEM found that the distribution of Si and Y are even, and Si can promote the diffusion of elements. In the Ni-13Al-3Si-1Y coating, SiO2 was oxidized for 30 h, and the non-dense oxide layer would peel off quickly. Higher Al concentration, the more difficult form SiO2 . Al and Ni are preferentially oxidized in oxidation process. Abstract: Three types of NiAlSiY coatings with different aluminum concentration were prepared. The isothermal oxidation behavior and mechanism of coatings at 500 °C were studied. The results indicate a multilayer oxide layer composed of NiO outer layer and Al2 O3 inner layer is formed on the surface. The diffusion of aluminum in the coating and the phase transition from β-NiAl to γ'-Ni3 Al promote the formation of Al2 O3 . Silicon plays an important role in the diffusion of aluminum by refining grains. When the aluminum is 21 wt.%, a dense Al2 O3 layer can be formed on the NiAlSiY coating after oxidation for 30 h.